Endosalpingiosis with concurrent endometriosis of ovary masquerading as ovarian malignancy - Shah, Amita; Zangmo, Rinchen; Jain, Kalpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Endosalpingiosis is a rare gynecological disorder of müllerian origin, characterized by the presence of tubal epithelium outside the fallopian tube, which involves structures of the female genital tract, peritoneum, and sub-peritoneal tissues. Endosalpingiosis can be associated with endometriosis or endocervicosis, although it often appears alone. Authors report a case of endosalpingiosis with concurrent endometriosis in a 42-year-old P2L1 patient. The patient presented to us with complaints of heaviness in lower abdomen, a feeling a lump in the lower abdomen and low-grade fever for 15 days. On per abdominal examination, a large solid cystic mass up to 20 weeks size was felt, which was more on the left side. Cervix was normal on speculum examination, the same mass was felt on per vaginal examination, separate from the uterus, the right fornix appeared free. Patient was asked to get a set of investigations done and to review as early as possible. An exploratory laparotomy with peritoneal wash cytology, total abdominal hysterectomy, bilateral salpingo-ophorectomy with supracolic and infracolic omentectomy and bilateral pelvic lymph nodes dissection was done on 18/07/18. Per operatively, there was a large cystic mass occupying the abdominal cavity adhered to the bowel and to posterior wall of the uterus, adhesiolysis followed by staging laparotomy was done. Patient’s postoperative course was uneventful and she was discharged on the 5th day of surgery in stable condition. The final histopathology report was suggestive of endosalpingiosis with concurrent endometriosis.